Transferability and Upscaling of Fuzzy Classification for Shoreline Change over 30 Years - Dewi, R. (2020)
The results also show an agreement of water membership values between the reference and target subsets indicated by κ > 0.82. Over the study period, the area exhibited both erosion and accretion. The erosion was indicated by changes into water and changes from non-water into shoreline were observed for approximately 78 km2. Accretion was due to changes into non-water and changes from water into shoreline for 19.5 km2. Erosion was severe in the eastern section of the study area, whereas the middle section gained land through reclamation activities. These erosion and accretion processes played an active role in the changes of the shoreline. We conclude that the method is applicable to the current study area. The relation between land use/cover classes and the value of FCM parameters produced in this study can be adopted.